Interval sliding mode observer design for linear and nonlinear systems. (January 2018) - Oubabas, Hocine; Djennoune, Said; Bettayeb, Maamar
Highlights: New interval sliding mode observers design based on convex weighted sum of an upper and a lower estimators for both linear and nonlinear systems. Convergence analysis using Lyapunov stability theory. Applications to bioprocess described by a linear model and to isothermic reactor described by nonlinear model. Abstract: In this paper, an interval sliding mode observer design method for uncertain systems is proposed. Uncertainty is assumed between a known minimum value and a maximum value. The observer is then constructed via a convex weighted sum of an upper estimator corresponding to the maximum value of the uncertainty and a lower estimator corresponding to the minimum value of the uncertainty. The weighting factor is calculated at each time, from the different measured outputs and the bounds of the interval of the estimator.